1971
DOI: 10.1159/000220718
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lifespan of Leukemic Mice Treated with Drugs Related to (–)-Emetine

Abstract: The lifespan of mice bearing ascitic leukemia L1210 could be prolonged by treatment with (-)-emetine dihydrochloride. Optimal dosage schedules required emetine administration daily for 5 days (QD, day 1–5) or intermittently on every 4th day. (Q4D, day 1, 5, 9). Compounds related to (-)-emetine which are active in other biological systems, having the correct stereospecific structure at the C-1′ position in the molecule, a secondary amine structure at N-2′ and an ethyl-group substituent at C-3 were also effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1974
1974
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…In recent years several proteins have been found to possess anti-cancer properties and their possible use in the treatment of human cancer is being explored (Eking and Montgomery, 1979;Griffin et al, 1978;Jondorf et al, 1971;Sawyer et al, 1979). The toxic plant proteins abrin and ricin studied here have little effect on the bone marrow, and are therefore interesting candidates for combination therapy with conventional cytostatic agents having myelosuppression as a dose-limiting side-effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years several proteins have been found to possess anti-cancer properties and their possible use in the treatment of human cancer is being explored (Eking and Montgomery, 1979;Griffin et al, 1978;Jondorf et al, 1971;Sawyer et al, 1979). The toxic plant proteins abrin and ricin studied here have little effect on the bone marrow, and are therefore interesting candidates for combination therapy with conventional cytostatic agents having myelosuppression as a dose-limiting side-effect.…”
Section: Discussionmentioning
confidence: 99%
“…We have, therefore, investigated antibody formation against abrin and ricin in treated cancer patients and in mice, using a highly sensitive enzyme-linked immunosorbent assay (ELISA). The results may be of interest also for the use of other foreign proteins with carcinostatic properties (Elting and Montgomery, 1979;Griffin et al, 1978;Jondorf et al, 1971;Sawyer et al, 1979), as well as for the clinical application of monoclonal antibodies, including their use as carriers for toxic proteins such as abrin and ricin or their A-chains (for review see Olsnes and Pihl, 1982b).…”
mentioning
confidence: 99%
“…For determining the life-span of tumour-bearing mice, groups of ten animals were inoculated with Ehrlich ascitesor sarcoma 180-tumour cells as above. Groups other than saline-treated controls received (-)-emetine or (-)-O-methyltubulosine according to dosage schedules based on those found to be optimal for the treatment of mice bearing asciticleukaemia L1210 cells (Jondorf et al, 1971). Animals found dead in the mornings were considered to have survived the previous day for the purpose of calculating mean survival times of the variously treated groups.…”
Section: Methodsmentioning
confidence: 99%
“…Numbers in parenthesis are range of values observed. (Jondorf et al, 1971), are definitely carcinostatic ,but do not completely eradicate Ehrlich ascites or sarcoma 180 cells.…”
Section: Methodsmentioning
confidence: 99%
“…As discussed in our earlier study (15), Emetine acts as an effective chemotherapeutic agent by increasing the lifespan of tumor-bearing mice (16,17) and thus has the possibility for clinical advantage (18,19). However, although no previous study explains the mechanism responsible for the anti-tumor effect of Emetine, our results regarding the effects of Emetine on Bcl-x splicing (15) suggested that Emetine promoted the expression of pro-apoptotic proteins by regulating alternative splicing.…”
mentioning
confidence: 93%